O.ÁBDIRAXMANOVTÍŃ SATIRALÍQ SHÍǴARMALARÍNDA OBRAZ JASAW SHEBERLIGI - Seytbekov, A.B. (ILIM hám JÁMIYET, 2025)
The article focuses on the study of O.Abdurahmonov’s skill in creating characters in his satirical works. In particular, the issue of image and character was analyzed based on the writer’s stories.